Tujuan - Wahyu Isra Deni; afdhal afdhal (JURNAL BUANA, 2020)
The purpose of this research is for 1). Know how the water facilities are convening in the village of the Stake River. 2). Learn how Mckin The stake River Village is. 3). Find out how the waste disposal means in the village of the Stake River. 4). Find out how waste water disposal means in the village of the Stake River. This research is liquid descriptive research. Data used is primary. There were 74 people being samples of research respondents who were in 4 hamlets located in the village of Pasak River. Data retrieval by means of spreading Angket and analyzed using data analysis technology according to Ari Kunto. The results of this research are: 1). The availability of clean water facilities registered adequate but (10%) The river water is classified as clean. 2). Registered MCK conditions meet the terms and conditions of 95% of households with bathrooms and latinies. 3). Registered garbage disposal conditions meet the health requirements of the environment can be seen from 27% of people throw waste in their home trash, 68% of people throw waste in the land of quarry yard and 5% people throw waste directly to TPA. 4). The condition of waste air discharge has not qualified environmental health requirements can be seen from 7% unreachable communities of waste channels, 20% of the community's affordable waste channel of river Glory, 41% of affordable Community channels Waste of pool and 32% of people who have a waste channel of irrigation channels. Keywords: MCK environment, Health, response